Optical demultiplexer using a holographic concave grating for POF–WDM systems - Bartkiv, Lyubomyr V.; Bobitski, Yaroslav V.; Poisel, Hans (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Polymer optical fiber (POF) is one of the best transmission media for short-distance communications. To increase the transmission capacity of the fiber a wavelength-division-multiplexing (WDM) technique is commonly used. Several POF-WDM systems have been realized using interference filters and plane diffraction gratings as wavelength selective elements. In the present paper, for the first time a concave diffraction grating is applied with POF. A holographic concave grating is calculated and optimized for the use in an optical demultiplexer. The optical losses in the designed demultiplexer are estimated theoretically.
Optica Applicata, Vol. 35, 2005, nr 1, s. 59-66
Keywords: optyka; polymer optical fiber (POF); holographic concave grating; optical demultiplexer